Eko-Teologi: Etika Kristen dalam Memenuhi Tujuan Ekosistem pada Tujuan Pembangunan Berkelanjutan - Erastus Sabdono (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
The environmental damage that is happening today, such as climate change, deforestation, and ocean pollution, demands a holistic and cross-sectoral response. In this context, religion can play a significant role in shaping human mindsets and behaviours towards nature. Eco-theology is a theological approach that integrates concern for the environment in the context of the Christian faith. With reference to the Sustainable Development Goals (SDGs), specifically those related to ecosystems such as Goal 13 (Climate Action), Goal 14 (Ocean Ecosystems), and Goal 15 (Terrestrial Ecosystems), eco-theology offers an ethical framework to encourage collective responsibility for creation. The approach used is qualitative descriptive through literature study. As a result, this article explores the principles of Christian ethics that can support the achievement of the goals of the SDGs ecosystem, including sustainable resource management, ecological justice, and environmental spirituality. With a multidisciplinary approach, this article demonstrates the relevance of eco-theology in answering global ecological challenges. As an implementation, eco-theology can be carried out through the Green Church Community, Ecological Liturgy, and Faith-Based Environmental Education.